Perancangan Sistem Informasi Harga Pokok Produksi Rumah Makan Menggunakan Metode Recipe-Based Full Costing - Kartono Kartono; Sandi Tendean; Riyadi Jimmy Iskandar (Universitas Budi Luhur, 2026)
Calculating the Cost of Production (CoP) is a crucial factor in determining selling prices and controlling costs within the restaurant business. The primary issue that frequently arises is cost distortion (under-costing distortion variance) caused by unstructured and conventional record-keeping, which can cause losses of up to 15% of net profit. This study aims to design a CoP information system utilizing the Recipe-Based Full Costing method for culinary Micro, Small, and Medium Enterprises (MSMEs) in Pontianak, and to evaluate its accuracy in comparison to the conventional method. The Rapid Application Development (RAD) method was employed for software development to enable rapid iteration with the users. The developed information system integrates raw material data, recipes, labor costs, and production overhead costs. The production cost for each menu item is calculated based on the quantity of raw materials specified in each recipe alongside the allocation of other production costs. Evaluation results show that the system is capable of correcting the under-costing problem, with a CoP discrepancy of IDR 1,300 per serving compared to the conventional method. Functionality evaluation using Black Box testing revealed a 100% functional success rate. System Usability Scale (SUS) testing yielded a score of 85, indicating a high level of user acceptance. The contributions of this study are divided into a methodological contribution through a cost comparison model and a technical contribution in the form of a proportionally automated operational cost allocation algorithm.